Analysis of HIV Diversity Using a High-Resolution Melting Assay - Towler, William I.; James, Maria M.; Ray, Stuart C.; Wang, Lei; Donnell, Deborah; Mwatha, Anthony; Guay, Laura; Nakabiito, Clemensia; Musoke, Philippa; Jackson, J. Brooks; Eshleman, Susan (AIDS research and human retroviruses, 2010)
HIV viruses are usually genetically homogeneous shortly after infection, and become more heterogeneous over time. We developed a high-resolution melting (HRM) assay to analyze HIV diversity without sequencing. Plasma samples from the HIVNET 012 trial were obtained from nine Ugandan mother–infant pairs. DNA amplified from the HIV gag region was analyzed to determine the number of degrees over which the DNA melted (HRM score). HRM gag DNA was also cloned and sequenced (50 clones/mother; 20 clones/infant). The median HRM score for infants (4.3, range 4.2–5.3) was higher than that for control plasmids (3.4, range 3.2–3.8, p < 0.001) and lower than that for mothers (5.7, range 4.4–7.7, p = 0.005, exact Wilcoxon rank sum test). The intraclass correlation coefficient reflecting assay reproducibility was 94% (95% CI: 89–98%). HRM scores were also compared to sequenced-based measures of HIV diversity; higher HRM scores were associated with higher genetic diversity (p < 0.001), complexity (p = 0.009), and Shannon entropy (p = 0.022), but not with length variation (p = 0.111). The HRM assay provides a novel, rapid method for assessing HIV diversity without sequencing. This assay could be applied to any region of the HIV genome or to other genetic systems that exhibit DNA diversity.